Synthesis, characterization and thermo-responsive behavior of end-functionalized poly(N-isopropylacrylamide) - Ilboga, Serzen; Coskun, Mehmet (Maik Nauka/Interperiodica/Springer, 2014)
N-Isopropylacrylamide was polymerized by atom transfer radical polymerization using 2-hydroxyethyl 2-chloropropionate and glycidyl 2-chloropropionate as initiators and CuCl/tris[2-(dimethylamino)ethyl]amine as the catalyst system in acetonitrile/water (10/1 v/v) at room temperature to afford an end-functionalized poly(N-isopropylacrylamide) with 2-hydroxyethyl and epoxy groups. Epoxy ring in glycidyl 2-chloropropionate was opened with tris(hydroxymethyl)aminomethane. The thermal phase transitions of aqueous solutions of synthesized polymers were studied; as expected hydrophilic end-group increased the lower critical solution temperature (LCST) while hydrophobic end-group decreased the LCST. All the polymers were characterized by means of FTIR and H-1 NMR spectroscopy.
Keywords: N-Isopropylacrylamide; Raft Polymerization; Aqueous-Solutions; Block-Copolymers; Molecular-Weight; Temperature; Transition; Microgels; Brushes; Release